Gestión de tecnología de información para gobiernos inteligentes: Un enfoque de arquitectura empresarial (2023)
Governments are advancing in the modernization of the public sector through ICT, facilitating the relationship between the state and citizens. Therefore, the need arises to develop business architectures that allow the alignment of institutional objectives and technological infrastructure through the integration of information systems, processes and people. In order to analyze the impact of Enterprise Architectures on Intelligent Government, five indexes E-Government, EParticipation, OpenData, OpenGoverment and Global Innovation are analyzed. © 2017.